An integrative approach in measuring hub-port supply chain performance: Potential contributions of a logistics and transport data exchange platform. Issue 2 (June 2016) - Cheng, Michael C.B.; Wang, James J.
Highlights: Through case study of a logistics and transport data exchange platform, we demonstrate that by connecting related documents such platform can perform some basic functions of a supply chain performance measurement (SCPM) system. We clearly explain the possible methods to enhance the integrative functions of a platform-based SCPM so that supply chain activities of infrastructure and institution stakeholders could also be monitored. Most importantly some new performance metrics that evaluate activities of different supply chain hierarchical parties are illustrated, which would be captured by the proposed integrative platform-based SCPM system. Finally, 3 policy options are suggested to the government of Hong Kong who may actually turn our proposed platform-based SCPM into reality. Abstract: The widespread globalization of production corporations in the late 20th century, as well as the subsequent trade facilitation policies of state authorities, generates an imperative need to extend the scope of supply chain management. Apart from the evaluation and monitoring of networked operations in different parts of the world, the effectiveness of trade policy measures is also included. This paper examines the potential contributions of a logistics and transport data exchange platform in measuring the performance of supply chain stakeholders of a hub port at different stages along the chain. A case study demonstrates how the integrative characteristics of a logistics and transport data exchange platform can be exploited to measure performances of different parties along the supply chain of a firm. More importantly, the authors explain how such a platform can be transformed into a system that evaluates the integrative supply chain activities of firm, the infrastructure, and the institutional stakeholders. A series of new supply chain performance metrics, including specific monitor end-to-end processes, can be captured by the proposed system. The paper concludes that in view of the significant policy implications of a platform-based supply chain performance measurement (SCPM) system, state intervention is critical to foster a high participation rate of the logistics and transport data exchange platform and develop its SCPM functions.